Question
upstudy study bank question image url

For the given equation, list the intercepts and test for symmetry. \( y=x^{2}-x-72 \)

Ask by Ortiz Rodriguez. in the United States
Jan 31,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

**Intercepts and Symmetry for \( y = x^{2} - x - 72 \):** - **Y-Intercept**: \( (0, -72) \) - **X-Intercepts**: \( (9, 0) \) and \( (-8, 0) \) - **Symmetry**: The graph is symmetric about the vertical line \( x = \frac{1}{2} \). It is not symmetric about the y-axis or the origin. --- **Graphical Summary:** - The parabola opens upwards. - It crosses the y-axis at \( (0, -72) \). - It crosses the x-axis at \( (9, 0) \) and \( (-8, 0) \). - The axis of symmetry is the vertical line \( x = \frac{1}{2} \).

Solution

To analyze the equation \( y = x^{2} - x - 72 \), we'll determine its intercepts and examine its symmetry. ### **Intercepts** 1. **Y-Intercept**: - **Definition**: The y-intercept occurs where \( x = 0 \). - **Calculation**: \[ y = (0)^2 - (0) - 72 = -72 \] - **Y-Intercept**: \( (0, -72) \) 2. **X-Intercepts**: - **Definition**: The x-intercepts occur where \( y = 0 \). - **Equation to Solve**: \[ 0 = x^{2} - x - 72 \] - **Solving the Quadratic Equation**: \[ x = \frac{1 \pm \sqrt{1 + 288}}{2} = \frac{1 \pm \sqrt{289}}{2} = \frac{1 \pm 17}{2} \] - **First Solution**: \[ x = \frac{1 + 17}{2} = \frac{18}{2} = 9 \] - **Second Solution**: \[ x = \frac{1 - 17}{2} = \frac{-16}{2} = -8 \] - **X-Intercepts**: \( (9, 0) \) and \( (-8, 0) \) ### **Symmetry** 1. **Y-Axis Symmetry**: - **Test**: Replace \( x \) with \( -x \) in the equation and see if it remains unchanged. - **Check**: \[ y = (-x)^{2} - (-x) - 72 = x^{2} + x - 72 \neq y \] - **Conclusion**: *Not symmetric* about the y-axis. 2. **Origin Symmetry**: - **Test**: Replace \( x \) with \( -x \) and \( y \) with \( -y \). - **Check**: \[ -y = (-x)^{2} - (-x) - 72 \implies -y = x^{2} + x - 72 \neq y \] - **Conclusion**: *Not symmetric* about the origin. 3. **Axis of Symmetry**: - **Definition**: For a quadratic equation \( y = ax^{2} + bx + c \), the axis of symmetry is the vertical line \( x = -\frac{b}{2a} \). - **Calculation**: \[ x = -\frac{-1}{2 \times 1} = \frac{1}{2} \] - **Conclusion**: The graph is symmetric about the **vertical line \( x = \frac{1}{2} \)**. ### **Summary** - **Intercepts**: - **Y-Intercept**: \( (0, -72) \) - **X-Intercepts**: \( (9, 0) \) and \( (-8, 0) \) - **Symmetry**: - The graph is **symmetric** about the **vertical line \( x = \frac{1}{2} \)**. - It is **not symmetric** with respect to the y-axis or the origin. --- **Graphical Representation:** Below is a sketch of the quadratic function \( y = x^{2} - x - 72 \): ``` ^ y | | * | | | | | * | | | | | | (-8,0) (9,0) | +----------------------------> x (0,-72) ``` - The vertex lies on the line \( x = \frac{1}{2} \). - The parabola opens upwards since the coefficient of \( x^{2} \) is positive.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the intercepts of the equation \( y = x^2 - x - 72 \), we set \( y = 0 \) to find the x-intercepts. Solving \( x^2 - x - 72 = 0 \) gives us \( x = 9 \) and \( x = -8 \). For the y-intercept, set \( x = 0 \), giving us \( y = -72 \). So the intercepts are \( (9, 0) \), \( (-8, 0) \), and \( (0, -72) \). Now, let's test for symmetry. A function is symmetric about the y-axis if \( f(-x) = f(x) \) and symmetric about the x-axis if \( -f(x) = f(x) \). In our case, \( f(-x) = -x^2 + x - 72 \) clearly isn't equal to \( f(x) = x^2 - x - 72 \), and checking for x-axis symmetry also shows they're not equal. Therefore, the function is neither y-axis nor x-axis symmetric!

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy